If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6w + 3 = 0 Reorder the terms: 3 + 6w = 0 Solving 3 + 6w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 6w = 0 + -3 6w = 0 + -3 Combine like terms: 0 + -3 = -3 6w = -3 Divide each side by '6'. w = -0.5 Simplifying w = -0.5
| 3x+-9=-57-8x | | 5+3*2-10/0+10= | | x/4-5=1 | | =[x-(4-i)][x-(4+i)] | | 2(7x-1)=-44 | | 3x^2+6=1 | | 2a-24-3=5a | | -3-5*-5^2-1/(-7)^2-(-3) | | 8x+70=3x-5 | | x+29=8x | | 75(3x)= | | 4b-4=2b+8 | | 8x+70=3x+5 | | 0.1-x=0.03 | | P=3r-7w | | x+29=4x | | 4x^2+8x=1 | | 6n^0*9n^0+8= | | 3x+x+1=12-7x | | e^x^(2/18) | | (2)1/2a=-25 | | (3/10)2 | | e^x^2/18 | | 4x*4x-12x+3=-15 | | 28-5x=-7 | | 2x^4-x=0 | | -4x+y=76 | | 7x-12=-138 | | -5-8d=-9d | | 1231234x+22=.45 | | 10-4X=-1/5-3/5X | | -7k=-7-8k |